Transition for adolescents with a rare disease: results of a nationwide German project - Oberste-Berghaus, Corinna; Höppner, Jakob; Burgard, Peter; Schündeln, Michael Maria; Matar, Nora; Müller, Gabriele; Krude, Heiko; Berner, Reinhard; Lee-Kirsch, Min Ae; Hauck, Fabian; Wainwright, Kerstin; Baumgarten, Sylvana; et al. (Orphanet journal of rare diseases, 2023)
The transition process from paediatric/adolescent to adult medical care settings is of utmost importance for the future health of adolescents with chronic diseases and poses even more difficulties in the context of rare diseases (RDs). Paediatric care teams are challenged to deliver adolescent-appropriate information and structures. Here we present a structured transition pathway which is patient-focused and adoptable for different RDs.
Gesehen am 15.06.2023